The Existence of Los Lambuang as a Culinary Tourist in Bukittinggi 1987 - 2019: Eksistensi Los Lambuang Sebagai Wisata Kuliner Di Bukittinggi 1987 - 2019 - Zidan; Zulfa; Meri Erawati (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2024)
This research discusses the existence of Los Lambuang as a Culinary Tourism in Bukittinggi (1987-2019), therefore the aim of this is to find out the history of the establishment of Los Lambuang in Bukittinggi, find out the existence of Los Lambuang as a culinary tourism in Bukittinggi City and find out the impact of Covid 19 on traders in Los Lambuang. This research method is a historical method, namely, heuristics, source criticism, interpretation and historiography. The results of this research explain the existence of Los Lambuang as a culinary tourist attraction in Bukttinggi